THE SOCIOSOMATIC DIMENSION OF ILLNESS. ROLE AND CONTRIBUTIONS OF MEDICAL ANTHROPOLOGY IN CLINICAL PRACTICE - DE BRABANTER, Geoffroy (MEDECINE LEGALE DROIT MEDICAL, 2025)
Medical anthropology is the branch of social anthropology which studies the cultural foundations of health beliefs and practices. Medical anthropologists consider the way in which different persons can perceive the causes, the mechanisms, the meanings and the consequences of a certain illness, and the expectations they have regarding health care professionals or services. These various considerations are rallied behind what we call “explanatory models” of illness. Clinical encounters in which certain patients are linked with caregivers can be the place of a sometimes violent opposition between several contradictory explanatory models. But rather than imposing the superiority of one model over another, the two parties can co construct the meaning of the problem in question. Starting from case studies, we will show how the specific “sociosomatic” dimension of illness – which is nearly inexistent in the classical biomedical conception of illness – can offer a new perspective on the clinical reality for a better patient management.